Relationship of Cognitive Function to Motor Symptoms and Mood Disorders in Patients With Isolated Dystonia. Issue 1 (March 2017) - Foley, Jennifer A.; Vinke, R. Saman; Limousin, Patricia; Cipolotti, Lisa
Abstract : Objective: To investigate the relationship of dystonia symptoms to cognitive function by comparing cognitive performance in patients with focal (cervical) and generalized dystonia subtypes and examining the differential contributions of severity of symptoms and mood disorders to cognition. Background: Studies of the nonmotor syndrome in isolated dystonia have reported evidence of cognitive dysfunction, but the cause of this impairment remains unclear. Several studies have suggested that poor cognitive performance reflects the distracting effects of the motor symptoms and/or a mood disorder. Methods: In this retrospective study, we used an extensive battery of cognitive and mood assessments to compare 25 patients with cervical dystonia, 13 patients with generalized dystonia, and 50 healthy controls. Results: We found cognitive performance to be independent of all clinical and mood variables. We found no significant differences in cognition between the two dystonia groups. The combined dystonia groups had significant impairment on only one measure of cognitive function, the Trail Making Test. Two patients were also impaired on the Stroop test, and six on the Hayling Sentence Completion Test. Conclusions: The nonmotor features of dystonia include subtle cognitive symptoms and high rates of mood disorders, both of which occur independent of motor symptom severity and level of disability. Thus, we would argue that isolated dystonia is a tripartite disorder, with motor, affective, and subtle cognitive features.